2018
DOI: 10.1371/journal.pone.0205437
|View full text |Cite
|
Sign up to set email alerts
|

Blood cytokine expression correlates with early multi-organ damage in a mouse model of moderate hypothermia with circulatory arrest using cardiopulmonary bypass

Abstract: Cardiopulmonary bypass (CPB) with moderate hypothermic cardiac arrest (MHCA) is essential for prolonged complex procedures in cardiac surgery and is associated with postoperative complications. Although cytokine release provoked through MHCA under CPB plays a pivotal role in postoperative organ damage, the pathomechanisms are unclear. Here, we investigated the cytokine release pattern and histological organ damage after MHCA using a recently described mouse CPB model. Eight BALB/c mice underwent 60 minutes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 56 publications
(42 reference statements)
4
18
0
Order By: Relevance
“…We also found that activation of TLR signaling in myeloid cells was initially suppressed but later increased at 8h after surgery, agreeing with a previous report (21). Other major pathways activated by CPB were early cell proliferation, likely due to the margination of leukocytes and their precursors from bone marrow (22); post-CPB leukocyte migration as reported in the literature (15,16).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We also found that activation of TLR signaling in myeloid cells was initially suppressed but later increased at 8h after surgery, agreeing with a previous report (21). Other major pathways activated by CPB were early cell proliferation, likely due to the margination of leukocytes and their precursors from bone marrow (22); post-CPB leukocyte migration as reported in the literature (15,16).…”
Section: Discussionsupporting
confidence: 92%
“…The mechanism of how systemic inflammation leads to organ damage is unclear. Evidence of CPB-activated leukocytes transmigrating and infiltrating into tissues is substantial in the literature (14)(15)(16) and our results further corroborate that CPB-activated THP-1 cells rapidly upregulated adhesion and migration markers after shear. ~24.7% of the sheared monocytes later differentiated into macrophages; and together with the live inflammatory monocytes, they secrete cytokines, chemokines, and other damaging soluble factors to the surrounding tissues.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Clinical chemistry was done using an Olympus analyzer (AU 400) according to the manufacturer's instructions to evaluate liver enzymes (glutamate oxaloacetate transaminase (GOT) and glutamate pyruvate transaminase (GPT)) and kidney function (creatinine, urea) after vv-ECMO. All values were corrected for hemodilution as previously described [13]. Furthermore, to evaluate hemolysis during the experiment, lactate dehydrogenase (LDH) values were compared between the start of the experiment and after 4 hours.…”
Section: Blood Tests Of Kidney and Liver Functionmentioning
confidence: 99%
“…Twomicrometer paraffin sections were stained with periodic acid-Schiff (PAS) to evaluate kidney and liver morphology. Assessment of acute kidney injury (AKI) and liver damage was done using a method previously described [13].…”
Section: Histologymentioning
confidence: 99%